A prospective study of the rate of falls before and after cataract surgery. Issue 5 (1st May 2003) - Brannan, S; Dewar, C; Sen, J; Clarke, D; Marshall, T; Murray, P I
Abstract : Background: There has been considerable interest in the development of intervention programmes aimed at reducing the risk of falls. The primary objective was to ascertain whether cataract surgery reduced the risk of falls in elderly patients with age related cataract. Methods: 97 patients scheduled for cataract surgery were enrolled in this prospective clinical study. The patients were assessed for established risk factors for falls preoperatively and postoperatively. Patients were issued with a diary to record any falls and phoned at 2 monthly intervals during the 6 month preoperative and postoperative periods. Results: Of the 84 patients who completed the study, 31 recorded falls during the preoperative period (37%). This group showed a statistically significant reduction in the number of fallers in the postoperative period (n = 6, p<0.001) Conclusion: These results suggest that cataract surgery is an effective intervention to reduce the risk of falls in elderly patients with cataract related visual impairment.